2017
DOI: 10.1007/s40858-017-0198-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis of introduction and spread of huanglongbing in citrus groves in Rio Grande do Sul, Brazil

Abstract: Huanglongbing (HLB), the most damaging disease of the citrus industry, is present in the Brazilian states of São Paulo, Minas Gerais and Paraná. The risks of introduction and spread of this A1 quarantine pest in citrus groves of the Rio Grande do Sul (RS) state were assessed based on a structured questionnaire composed of 27 questions applied to 163 growers in 35 municipalities. The locations were defined according to the economic relevance of citriculture, and the sample size (number of interviewed farmers) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
(23 reference statements)
1
5
0
1
Order By: Relevance
“…In São Paulo State, HLB has forced more than five thousand farms to shift to another crop or to merge together with other farms from 2007 to 2018 (Bassanezi et al 2020). Finally, our results can be of value to further improve risk assessment of HLB spread should it be introduced to regions that share similarities with South of Minas and Central MG such as the major tangerine production in the eastern regions of Rio Grande do Sul state and for which only qualitative assessment was performed (Sulzbach et al 2018).…”
Section: Discussionmentioning
confidence: 80%
“…In São Paulo State, HLB has forced more than five thousand farms to shift to another crop or to merge together with other farms from 2007 to 2018 (Bassanezi et al 2020). Finally, our results can be of value to further improve risk assessment of HLB spread should it be introduced to regions that share similarities with South of Minas and Central MG such as the major tangerine production in the eastern regions of Rio Grande do Sul state and for which only qualitative assessment was performed (Sulzbach et al 2018).…”
Section: Discussionmentioning
confidence: 80%
“…Despite very important to the orchard phytosanitary, the pruning is not constituted in a management tool of HLB (ROUSE et al, 2017;VASHISTH;LIVINGSTON, 2019). It is observed that, among the managements, the application of pesticides was the only one that obtained limited adoption level (39%) (Figure 3A), which can reflect the low technological pattern employed in the conduction of the orchards due to the low productivity (SULZBACH et al, 2018;ALVES et al, 2020). For example, for orange, the average productivity in the five municipalities evaluated is 5.374.4 kg.ha -1 (Table 1), while the baiana orange is of 11.255 kg.ha -1 (IBGE, 2018), data that do not corroborate the situation of the producers in the state of Rio Grande do Sul, where Sulzbach et al (2016) found average productivities similar to the average of the state.…”
Section: Orchard Managementmentioning
confidence: 99%
“…The population reduction of the vector insect is fundamental to the management of the HLB, and the use of pesticides is the most common control method. And for this, the non-adoption of this strategy or insufficient adoption is considered one of the main factors for the dissemination of the HLB (SULZBACH et al, 2018;ALVES et al, 2020).…”
Section: Orchard Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Nas Américas, o primeiro relato da doença se deu em 2004 no Brasil, na região de Araraquara, SP (COLETTA FILHO et al, 2004;TEIXEIRA et al, 2005), sendo que hoje também ocorre no Paraná e em Minas Gerais (BELASQUE JÚNIOR et al, 2009;BASSANEZI et al, 2013). Em 2012 foram detectados psilídeos infectivos na Bahia (BARBOZA et al, 2014), e o monitoramento desses insetos tem sido intensificado (SULZBACH et al, 2017). Um ano após o relato da doença em São Paulo, ela foi encontrada na Flórida, EUA (HALBERT 2005;SUTTON et al, 2005) e nos anos seguintes em outros Estados americanos, apesar da intensa fiscalização daquele país (HALBERT et al, 2010;KUMAGAI et al, 2013;DA GRAÇA et al, 2015).…”
Section: Estratégias Biotecnológicas Para O Manejo Do Hlbunclassified